DRYING, COLOUR AND REHYDRATION CHARACTERISTICS OF ORANGE SLICES UNDER INFRARED RADIATION HEATING - Doymaz, I (PLAPIQUI(UNS-CONICET), 2022)
The effect of different infrared (IR) powers on drying of orange slices was investigated in infrared dryer. The orange slices dried at 62, 74 and 88 W infrared powers and constant slice thickness of 6 mm. Results showed that drying, colour and rehydration characteristics of orange slices were greatly influenced by infrared power. The drying data were fitted with five mathematical models available in the literature. Based on the statistical tests applied to make an assessment, the model of Midilli and Kucuk was found to satisfactorily explain drying kinetics of orange slices for all drying conditions. The Fick's diffusion model was used to calculate the effective moisture diffusivity (D-eff) of orange slices. The values of D-eff varied from 1.59x10(-10) to 2.49x10(-10) m(2)/s. It was found that the D-eff increased with increasing IR power. Activation energy was estimated by a modified Arrhenius type equation as 2.11 kW/kg. As the infrared power increased, the rehydration ratio was found to be reduced. Furthermore, with increase of infrared power, the values of a and Delta E increased, whereas the values of L, b and C decreased.
Keywords: Activation energy; effective moisture diffusivity; infrared drying; modelling; orange slices; MOISTURE DIFFUSIVITY; KINETICS; DEHYDRATION; Engineering